2020
DOI: 10.1109/access.2020.2970314
|View full text |Cite
|
Sign up to set email alerts
|

Localized Bicep Tissue Bioimpedance Alterations Following Eccentric Exercise in Healthy Young Adults

Abstract: The localized bicep tissue bioimpedance was measured from participants who completed an eccentric exercise protocol with one arm and no exercise with the other arm to compare changes that occur as a result of the exercise protocol over a 96h observation period. Methods: The localized bicep bioimpedance, bicep circumference, and self-reports of bicep pain were collected from 6 volunteers at pre, post, 24h, 48h, 72h, and 96h timepoints after completing an eccentric exercise protocol of the elbow flexor muscles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 39 publications
6
28
0
Order By: Relevance
“…The bioimpedance data from the participants that was analyzed for this research was collected and reported initially by Freeborn et al in [16] . While the complete details of the study participants and exercise protocol are available in [16] , they are also summarized here for readers.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The bioimpedance data from the participants that was analyzed for this research was collected and reported initially by Freeborn et al in [16] . While the complete details of the study participants and exercise protocol are available in [16] , they are also summarized here for readers.…”
Section: Methodsmentioning
confidence: 99%
“…Bioimpedance is also currently being investigated as a noninvasive technique to characterize skeletal muscle tissue with a particular focus on assessing neuromuscular disorders [10] , [11] , [2] . Beyond assessing neuromuscular disorders, bioimpedance is being investigated to monitor tissue changes that result from the exercise and fatigue of skeletal muscle, with decreases in impedance magnitude reported after resistance training protocols [12] , [13] , [14] , [15] , [16] , with further results reporting decreased in impedance magnitude for acute muscle injury [17] , [18] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations